High-Speed MS/MS in Situ Imaging by Nanospray Desorption Electrospray Ionization Mass Spectrometry - Lanekoff, Ingela (2013)
Nanospray desorption electrospray ionization (nano-DESI) combined with tandem mass spectrometry (MS/MS), high-resolution mass analysis of the fragment ions (m/Δ=17,500 at m/z 200), and rapid spectral acquisition enabled simultaneous imaging and identification of a large number of metabolites and lipids from 92 selected m/z windows (± 1 Da) with a spatial resolution of better than 150 μm. Mouse uterine sections of implantation sites on day 6 of pregnancy were analyzed in the ambient environment without any sample pre-treatment. MS/MS imaging was performed by scanning the sample under the nano-DESI probe at 10 μm/s while acquiring higher-energy collision-induced dissociation (HCD) spectra for a targeted inclusion list of 92 m/z values at a rate of ~6.3 spectra/s. Molecular ions and their corresponding fragments, separated using high-resolution mass analysis, were assigned based on accurate mass measurement. Using this approach, we were able to identify and image both abundant and low-abundance isobaric and isomeric species within each m/z window. MS/MS analysis enabled efficient separation and identification of isomeric and isobaric phospholipids that are difficult to separate in a full-scan mode. Furthermore, we identified several metabolites associated with early pregnancy and obtained the first 2D images of these molecules.